Impact of New Coronavirus Epidemics on HIV-Infected Patients - Soriano, Vicente; Barreiro, Pablo (AIDS Reviews, 2020)
Since the first report of a cluster of pneumonia cases in Wuhan (China) at the end of 2019 due to a new airborne highly transmissible coronavirus known as SARS-CoV-2, large-scale spreading has rapidly become a global concern. Up to the end of February 2020, more than 85,000 cases had been confirmed worldwide, mostly in China, with more than 3,000 deaths. Figures are increasing on a daily basis, being unpredictable what will happen next. Table 1 summarizes figures for major outbreaks due to acute viral infections recorded during the past 50 years. © 2020, Publicaciones Permanyer
Keywords: SARS Virus; Coronavirus; severe acute respiratory syndrome; Scopus; JCR